A community-based Falls Management Exercise Programme (FaME) improves balance, walking speed and reduced fear of falling. Issue 2 (30th January 2014) - Yeung, Pui Yee; Chan, Wayne; Woo, Jean
<x content-type="archive" xml:space="preserve">Abstract</x> Background Although effective community falls prevention programmes for the older persons have been described, challenges remain in translating proven interventions into daily practice. Aim To evaluate the efficacy, feasibility and acceptability of a falls prevention programme that can be integrated into daily activities in a group of community-dwelling older adults with risk of falling. Method A cohort study with intervention and comparison groups was designed to evaluate a 36-week group-based falls prevention exercise programme (FaME) in the community setting. Participants were aged 60 years or older, had fallen in the past 12 months, had fear of falling with avoidance of activities or had deficits in balance control. Primary outcome measures included assessment of balance control and mobility; secondary outcome measures included level of physical activity, assessment of fear of falling and health-related quality of life. Results There were 48 and 51 participants in the intervention and comparison groups, respectively. There were improvements in measurements of balance, walking speed and self-efficacy. The drop out rate was low (14.6% and 3.9% from the intervention and comparison groups, respectively). Overall compliance in the intervention group was 79%. Factors that motivated continued participation include the regular and long-term nature of the programme helping to reinforce their exercise habits, the simplicity of movements and friendliness of the group. Conclusion The FaME programme improves balance, walking speed and reduces fear of falling. It could be widely promoted and integrated into regular health and social activities in community settings.